A quantitative comparative analysis of incoming and outgoing students’ perceptions in international student mobility - Chen, Zongsheng; Constantin, Cristinel Petrisor; Kelepouris, Christos (Journal of International Students, 2026)
International student mobility is essential to higher education internationalization, yet comparative quantitative research on incoming and outgoing students remains limited. In this study, motivations and attitudes toward cross-border education were analyzed by comparing 329 international students in China and 303 Chinese outgoing students using questionnaires. Data were examined via reliability and validity tests, mean comparisons, and structural equation modeling (SEM), with acceptable model fit indices. The findings show that incoming students prioritized postgraduate employment and scholarships, whereas outgoing students focused on cultural exploration and personal growth. Incoming students held more optimistic attitudes toward career benefits, policy support, and leadership engagement. Both groups supported peer mentoring but were neutral toward extended language courses and online learning. This study enriches theoretical frameworks and provides practical implications for universities and policy makers to design tailored strategies that improve student satisfaction and support sustainable international mobility.